Poems from Abakwa in Cameroon Pidgin English - Wuteh, Peter Wuteh (Book collections on Project MUSE., 2015)
"Poems from Abakwa in Cameroon Pidgin English is one patriotic rage. An anthology of sorts, this book of poems contains wisdom, inspirational reflections and witticisms for all. Through apt descriptions, illustrations, dialogues, interrogations and incisive phraseology, Peter Wuteh Vakunta creates an effective balance of colorful images that traces and documents disturbing accounts and evidences of corruption, greed, skewed values and life experiences that have assaulted his fatherland, betrayed political leaders and institutions, court judges, and parliamentarians as the police-cum-military continue to put their ambitions above the country's needs while forsaking future leaders-children. Vakunta describes how civil servants represent selfish interests and aspirations. Judges are intimidated as the nation's laws continue to be transgressed. The police and military continue to abuse the trust invested in them by civilians and misdirect their patriotism while virtually the entire nation continues to live shaky lives with a punctured integrity. Vakunta does this in popular lingos commonly used by musicians, business folks, and the common man under several labels-pidgin English, Camfranglais, Cam-tok, Camspeak, Majunga tok ..."--Dr. Fidelis Achenjang, Union College, USA.